2019
DOI: 10.2478/jomb-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum paraoxonase 1 activities, polymorphisms and oxidative stress in breast cancer patients with type 2 diabetes mellitus

Abstract: Summary Background The aim of the study was to investigate the association of paraoxonase 1 (PON1) polymorphism, PON1/arylesterase (ARE) activity and oxidative stress index (OSI) in breast cancer (BC) patients with type 2 diabetes (DM). Methods Our study group consisted of 30 healthy women (HV group) and 66 female BC patients. The BC patients were divided into two groups: those with (n=37) and without DM (n=29) (BDM and NBDM group). Genotyping of PON1 Q192R and L55M polymorphisms were done by polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…On the other hand, the QR genotype was more common in the control group compared with patients with nasal polyps. The distribution of the genotype in the control group of the study by Eraldemir et al [ 28 ] is compatible with our results. The major limitation of this study is the lack of information about the PON1 enzyme levels and activities in our study group.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the QR genotype was more common in the control group compared with patients with nasal polyps. The distribution of the genotype in the control group of the study by Eraldemir et al [ 28 ] is compatible with our results. The major limitation of this study is the lack of information about the PON1 enzyme levels and activities in our study group.…”
Section: Discussionsupporting
confidence: 93%
“…(3) show a highly significant increase (p≤ 0.01) in this index in serum and saliva of the pre-malignant and malignant breast tumor patient groups compared to the corresponding value in the control group. These results agree with the results of Feng et al, 2012 in China [18] and Eraldemir, 2019 in Turkey [20] reporting the presence of a high value of OSI in serum of studied breast cancer women with type 2 diabetes mellitus who underwent surgery compared to the control group This index was also observed to increase significantly (p≤ 0.01) in saliva and serum samples from women with breast cancer compared to the corresponding fluid from the premalignant (benign) group, a result that was in agreement with the result of the Sawczuk et al 2019 study that reported an elevated [OSI] in saliva from women with malignant tumor with and without mutation in BRCA1, (BRCA1 encodes a suppressor protein) [21]. As the disease progressed from pre-malignant to malignant stages, significant differences were observed among the three study groups as illustrated in Fig.…”
Section: Methodssupporting
confidence: 93%
“…24 Changes in PON1 activity attributed to the Q192R polymorphism can have a significant effect on oxidative conditions and disease exacerbation in individuals. 25 A study by Ferré et al showed that PON-192 polymorphism, along with other polymorphisms, contributes to changes in the host response to HCV infection. 26 Taken together, allelic frequency as well as the effects of ethnicityrelated factors on the PON1 activity may, at least in part, explain the differences in mortality and the prevalence of COVID-19 between various countries.…”
Section: Discussionmentioning
confidence: 99%
“…24 Changes in PON1 activity attributed to the Q192R polymorphism can have a significant effect on oxidative conditions and disease exacerbation in individuals. 25…”
Section: Discussionmentioning
confidence: 99%